Frames, framing and framing effects in cognitive CDA. (April 2023) - Hart, Christopher
In this paper I provide an account of frames, framing and framing effects from the perspective of cognitive linguistics as it is applied in critical discourse analysis. Frames, here, are understood as structured bundles of concepts accessed by linguistic expressions to constitute the meaning of an utterance or linguistic formulation. I describe frames at two levels: event-frames representing basic patterns of experience in domains like action and motion and frames representing areas of experience cultivated as members of a given culture. I show how the linguistic expressions selected in media discourses of political protests access frames and event-frames to construe the activities of social movements in a particular ideologically vested fashion, including figuratively as familiar frames such as the WAR frame are recruited to provide structure in the apprehension of the target situation. I show how such framing efforts are manifested in visual depictions as well as verbal descriptions of political protests. Finally, I describe recent experimental studies that provide evidence for metaphorical framing effects in audiences.